Risk Factors of Hypertension among Diabetic Patients from Yaoundé Central Hospital and Etoug-Ebe Baptist Health Centre, Cameroon - Beryl Kemche; Brice Ulrich Saha Foudjo; Elie Fokou (Journal of Diabetes Research)
Uncontrolled blood pressure is a threat to diabetic patients’ life. The aim of this study was to identify risk factors of hypertension among diabetic patients at different stages from Yaoundé Central Hospital and Etoug-Ebe Baptist Health Center of Cameroon. A hospital-based cross-sectional study was conducted for 6 months, and 109 participants (types 1 and 2), aged 24–81 years, were enrolled using simple random sampling. A pretested structured questionnaire was used to collect sociodemographic data, habitual behaviors, clinical history blood pressure, and anthropometric measures. The prevalence of hypertension was 86.2%. Of the total, 13.8% participants were normotensive, 32.1% stage 1 hypertensive, and 54.1% stage 2 hypertensive. Being a male (p=0.046) and not smoking (p=0.036) were negatively associated with stage 1 hypertension whereas eating less than 3 times (p=0.046) and duration of diabetes greater than 9 years among women (p=0.039) were positively associated. Age above 40 years (p=0.002) was negatively associated with stage 2 hypertension. However, age above 40 years had a negative effect among Christian, less educated diabetics, people having diabetes for more than 9 years, and those on medical treatment (5.556≤specific OR≤10.278). Duration of diabetes (age-adjusted OR=1.155; p=0.003) and abnormal waist circumference (crude OR=4.074; p=0.024) were positively associated with stage 2. Abnormal waist-to-hip ratio (crude OR=3.773; p=0.028) and feeding rate greater than 2 times a day (WHR-adjusted OR=3.417; p=0.046) were positively associated with hypertension (stages 1 and 2). This study suggests that hypertension, present at its two stages, is a serious health issue among diabetic patients. Thus, appropriate intervention should be put in place to prevent and control hypertension by managing identified risk factors.